Patient reported outcomes of duodenum-preserving pancreatic head resection in chronic pancreatitis: high effectivity is impaired by prolonged non-surgical management - Leonhardt, Carl-Stephan; Niesen, Willem; Pils, Dietmar; Angelova, Yoana; Hankeln, Thomas; Scheele, Christian; Hinz, Ulf; Hackert, Thilo; Büchler, Markus W.; Strobel, Oliver (HPB, 2024)
Background: Chronic pancreatitis (CP) causes suffering and socioeconomic burden. This study evaluated perioperative results and patient-reported outcomes (PRO) in CP patients treated with duodenumpreserving pancreatic head resection (DPPHR).Methods: Data were analyzed of CP patients undergoing DPPHR between 01/2001-10/2014. PROs were measured using a specifically designed questionnaire and the EORTC QLQ-C30/PAN26. Associations between treatment variables and PROs were examined.Results: Of 332 patients who received DPPHR, most (n = 251, 75.6%) underwent the Berne modification. Surgical morbidity was 21.5% (n = 71) and 90-day mortality 1.5% (n = 5). Median follow-up was 79.9 months, 5-year survival 90.5%, and 1.8% of patients developed pancreatic cancer. Of 283 patients alive, 178 (62.9%) returned questionnaires. Referral for surgery was self-initiated (38.0% of cases), by gastroenterologists (27.5%) and by general practitioners (21.1%). QoL improved in 78.7% of patients, remained stable in 12.1%, and worsened in 9.1%. Median Izbicki scores decreased from 90 to 5 points after surgery (p < 0.0001). Time from diagnosis to DPPHR was an independent, proportional predictor of a higher postoperative Izbicki score (p = 0.04).Conclusion: DPPHR is an effective, safe treatment for CP. A delay in surgery decreases surgical effectivity, hence CP patients should be referred to surgery early to ensure satisfactory outcomes.
Gesehen am 12.08.2024